Strengths of pelvic floor muscles in women with multiple sclerosis and its relationship with urinary incontinence and quality of life - Poorandokht Afshari; Parvin Abedi; Nastaran Majdinasab; Samaneh Tafakh; Mohammadhossein Haghighizadeh (Frontiers in Neurology)
BackgroundMultiple sclerosis (MS) is a debilitating autoimmune disease that mostly affects women.ObjectivesIn this study we evaluated the relationship of pelvic muscle strengths with urinary incontinence and quality of life in women with MS.Materials and methodsIn this cross-sectional study 87 women with MS were recruited. Data collected using a demographic questionnaire, the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF), and Quality of Life Questionnaire (QOL-SF-36). A perineometer was used to measure the strengths of pelvic muscle. Data analyzed using Pearson correlation test, and multiple linear regression tests.ResultsThere was a positive correlation between pelvic muscle strengths with all domains of quality of life except for body pain and role limitations due to emotional problems. A significant inverse correlation was found between urinary incontinence and all domains of quality of life except for body pain. Also, an inverse correlation was found between muscle strength and urinary incontinence (r = −0.838, p < 0.001). A one-unit increase in the quality of physical life was associated with a 0.15-unit increase in the strengths of pelvic floor muscles (p = 0.035). On the other hand, each additional year of marriage or disease duration significantly weakened pelvic floor muscles by 0.24 and 0.509 units, respectively (p < 0.05).ConclusionOur findings showed that pelvic muscle strength, urinary incontinence, and quality of life were significantly interrelated among female patients with MS. An inverse correlation was also found between muscle strength and urinary incontinence. Duration of marriage and length of MS disease were inversely associated with the strength of the pelvic floor muscles. Health providers are recommended to educate MS patients on the importance of pelvic muscle strengths.